The Healthy Native Youth Implementation Toolbox: Using Implementation Mapping to adapt an online decision support system to promote culturally-relevant sexual health education for American Indian and Alaska Native youth - Markham, Christine M.; Rushing, Stephanie Craig; Manthei, Jane; Singer, Michelle; Jessen, Cornelia; Gorman, Gwenda; Peskin, Melissa F.; Hernandez, Belinda F.; Sacca, Lea; Evans, Gabrielle S.; Luna-Meza, Claudia; Merritt, Zoe; et al. (Frontiers in Public Health, 2022)
Background: American Indian and Alaska Native (AI/AN) youth experience disparities in sexual and reproductive health, including the highest teen birth rate among racial/ethnic groups, and disproportionate rates of sexually transmitted infections. A growing number of evidence-based programs (EBPs) that integrate the strengths and cultural teachings of Native communities exist. Yet, multiple factors, including lack of trained personnel, limited resources, and geographic isolation, may hinder their adoption and implementation. Innovative implementation strategies that facilitate the adoption and implementation of sexual health EBPs in Native communities may help reduce these disparities. Methods: We applied Implementation Mapping, a systematic planning framework that utilizes theory, empirical evidence, and community input, to adapt a theory-based, online decision support system, iCHAMPSS (CHoosing And Maintaining Effective Programs for Sex Education in Schools), to support dissemination and implementation processes unique to Native communities. We used an iterative design process, incorporating input from Native practitioners and academicians, to ensure that the adapted support system reflects cultural identification, community values, and experiences. Results: Grounded in Diffusion of Innovations, Organizational Stage Theory, and Social Cognitive Theory, the Healthy Native Youth Implementation Toolbox supports Native practitioners through five phases (Gather, Choose, Prepare, Implement, and Grow) to adopt, implement, and maintain a culturally-relevant, age-appropriate sexual health EBP. The Toolbox provides tools, ready-to-use templates, and guidance to plan, implement, and grow a culturally-relevant adolescent health program with their Tribe or community. Hosted within the Healthy Native Youth website (www.healthynativeyouth.org), the Toolbox comprises: 1) a curriculum portal with access to fifteen culturally-relevant evidence-based health promotion programs; 2) a ‘resource library’ comprising 20+ support tools, templates, and links to external resources, and 3) ‘stories from the field’ comprising testimonials from experienced Native educators, who have implemented sexual health programs. Conclusions: There is a continued need to design, test, and evaluate D&I strategies that are relevant to Native communities. The Healthy Native Youth Implementation Toolbox contributes to the dissemination and implementation of evidence-based, culturally-relevant sexual health education programs in Native communities. Implementation Mapping provided a systematic approach to guide the adaptation process and integrate community voice with the goal of enhancing sexual health equity among AI/AN youth.